1991
DOI: 10.1113/jphysiol.1991.sp018396
|View full text |Cite
|
Sign up to set email alerts
|

Actions of ketamine, phencyclidine and MK‐801 on NMDA receptor currents in cultured mouse hippocampal neurones.

Abstract: SUMMARY1. Stable N-methyl-D-aspartic acid (NMDA) receptor-mediated currents in cultured mouse hippocampal neurones were evoked by 20 ms pressure pulse applications of L-aspartate, repeatedly applied at 30 or 40 s intervals, to the cell body region of the neurone. We have characterized the voltage-and use-dependent blockade of the currents by three dissociative anaesthetics: ketamine, phencyclidine (PCP) and MK-801 in mouse hippocampal neurones grown in dissociated tissue culture.2. We have used a simple model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
153
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(169 citation statements)
references
References 40 publications
14
153
0
Order By: Relevance
“…Binding and electrophysiological studies have demonstrated that PCP and MK-801 are superior noncompetitive inhibitors of, and have markedly higher affinity for, NMDA receptors than ketamine (Chen et al, 1959;Johnstone et al, 1959;Chen, 1965;McCarthy et al, 1965;Wong et al, 1986;MacDonald et al, 1991;Rogawski and Wenk, 2003). In addition, MK-801 block can occur across different membrane potentials, whereas PCP and ketamine inhibit NMDA receptors predominately at depolarized potentials (Halliwell et al, 1989;Dravid et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Binding and electrophysiological studies have demonstrated that PCP and MK-801 are superior noncompetitive inhibitors of, and have markedly higher affinity for, NMDA receptors than ketamine (Chen et al, 1959;Johnstone et al, 1959;Chen, 1965;McCarthy et al, 1965;Wong et al, 1986;MacDonald et al, 1991;Rogawski and Wenk, 2003). In addition, MK-801 block can occur across different membrane potentials, whereas PCP and ketamine inhibit NMDA receptors predominately at depolarized potentials (Halliwell et al, 1989;Dravid et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…MK-801, a dissociative anesthetic chemically unrelated to PCP, possesses an even greater affinity to, and inhibits NMDA receptors with higher potency than PCP (Wong et al, 1986;Huettner and Bean, 1988;MacDonald and Nowak, 1990;MacDonald et al, 1991). Furthermore, the blocking action of MK-801 on the NMDA receptor is less dependent on the membrane potential than ketamine or PCP (Halliwell et al, 1989;Dravid et al, 2007).…”
Section: ␣6␤2␦ Receptors Show High Sensitivity To Ketaminementioning
confidence: 99%
See 1 more Smart Citation
“…We previously proposed that SULFA acts as a potential open channel blocker (Ryu et al, 2003), but further experiments, reports and careful consideration have ruled out this possibility. Several channel blockers, including MK-801 (Halliwell et al, 1989), ketamine (MacDonald et al, 1991), and memantine (Chen and Lipton, 1997) have shown activity-and voltage-dependencies inconsistent with those observed for SULFA (Figs. 2B and 8).…”
Section: Molecular Mechanisms Underlying the Sulfa Blockade Of Nmda Smentioning
confidence: 99%
“…In contrast, low-affinity NMDA-receptor antagonists such as budipine [K i = 12 µM (41)] are clinically tolerated and are not typically associated with psychotomimetic side effects (42) on account of their fast dissociation kinetics [offset rate of budipine, 0.63 s −1 (43)] that are ≥2 orders of magnitude faster than that of MK-801 (44). During strong depolarization, low-affinity NMDA-receptor ion channel antagonists are thought to mimic Mg 2+ by rapidly leaving the ion channel after its physiologic activation, but differ from Mg 2+ in that it does not exit the ion channel after moderate prolonged synaptic depolarization, as seen with chronic excitotoxicity (40).…”
Section: Discussionmentioning
confidence: 99%